Editors' introduction: critical terrorism studies: reflections on policy-relevance and disciplinarity. Issue 1 (2nd January 2016) - Fitzgerald, James; Ali, Nadya; Armstrong, Megan
ABSTRACT: The articles in this special issue are drawn from papers presented at a workshop entitled "10 Years of Critical Terrorism Studies" and a conference entitled "Critical Terrorism Studies and Policy Relevance: Beyond Critique". The workshop and conference were organised by the Critical Studies on Terrorism Working Group of the British International Studies Association (BISA) and were held at the BISA Annual Conference in London on 15 June 2015 and the University of Leeds from 3 to 4 September 2015, respectively. The events aimed to explore the interrelationship between Critical Terrorism Studies (CTS) and policy-relevance, with particular regard to how it shapes and challenges the very disciplinarity of CTS. These events also aimed to explore the practicalities of engaging with/learning from practitioners, while questioning the normative and ethical consequences of choosing to engage or resist orthodox parameters of policy-making and/or creating alternative spaces for engagement. The articles in this issue reflect those aims.